Effectiveness of a community-based intervention on nutrition education of mothers of malnourished children in a rural coastal area of South India - G Pavithra; S Ganesh Kumar; Gautam Roy (Wolters Kluwer Medknow Publications, 2019)
Background: There is a paucity of evidence on improvement in malnutrition status after follow-up intervention among malnourished under-five children. Objective: The objective of the study is to assess the effect of community-based follow-up health education intervention on the awareness level of mothers, calorie intake, protein intake, and weight gain of malnourished children. Methods: This intervention study was conducted from December 2012 to October 2014 in three phases at rural Puducherry, coastal South India. The intervention group (57 mothers of 64 children) and control group (60 mothers of 64 children) included moderate and severely malnourished children aged 13-60 months. Children in the control group were taken from different areas and matched for age (±6 months) and sex. Health education intervention and follow-up supervision for 15 months were given to the mothers. Results: Awareness level in all domains increased significantly in the intervention group. In the intervention group, 81% (52) of malnourished children turned out to normal, whereas in the control group, 64% (41) of them became normal. There was a statistically significant difference between the mean changes in the protein intake among boys (15.34 g to 19.91 g in the intervention group against 13.6 g to 16.24 g in the control group) and girls (15.09 g to 19.57 g in the intervention group against 13.36 g to 16.51 g in the control group) and calorie intake among girls (993.86 kcal to 1116.55 kcal in the intervention group against 992.65 kcal to 1078.75 kcal in the control group) between the two groups. Conclusion: There was comparatively marginal increase in protein intake, calories' intake, and weight gain in the intervention group.